Electrocatalysis of N-doped Carbons in the Oxygen Reduction Reaction as a function of pH: N-sites and Scaffold Effects - Colavita, Paula (My University, 2019)
Metal-free nitrogenated amorphous carbon electrodes were synthesised via dc plasma magnetron sputtering and post-deposition annealing at different temperatures. The electrocatalytic activity of the electrodes towards the oxygen reduction reaction (ORR) was studied as a function of pH using cyclic voltammetry with a rotating disk electrode. The trends in onset potential were correlated to the carbon nanostructure and chemical composition of the electrodes as determined via Raman spectroscopy and X-ray photoelectron spectroscopy analysis. Results suggest that: 1) the ORR activity in acidic conditions is strongly correlated to the concentration of pyridinic nitrogen sites. 2) At high pH, the presence of graphitic nitrogen sites and a graphitized carbon scaffold are the strongest predictors of high ORR onsets, while pyridinic nitrogen site density does not correlate to ORR activity. An inversion region where pyridine-mediated activity competes with graphiticN mediated activity is identified in the pH region close to the value of pKa of the pyridinium cation. The onset of the ORR is therefore determined by the activity of different sites as a function of pH and evidence for distinct reduction reaction pathways emerges from these results.
PUBLISHED
Keywords: Electrocatalysis; Carbon electrodes; Nanoscience & Materials